2019
DOI: 10.1038/s41598-019-52764-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential Inhibitors of Galactofuranosyltransferase 2 (GlfT2): Molecular Docking, 3D-QSAR, and In Silico ADMETox Studies

Abstract: A strategy in the discovery of anti-tuberculosis (anti-TB) drug involves targeting the enzymes involved in the biosynthesis of Mycobacterium tuberculosis’ (Mtb) cell wall. One of these enzymes is Galactofuranosyltransferase 2 (GlfT2) that catalyzes the elongation of the galactan chain of Mtb cell wall. Studies targeting GlfT2 have so far produced compounds showing minimal inhibitory activity. With the current challenge of designing potential GlfT2 inhibitors with high inhibition activity, computational methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 77 publications
1
29
0
Order By: Relevance
“…It is known that ADMETox prediction is a significant part in evaluating if a drug can be toxic or absorbed during drug development process [48]. In our study, ADMETox evaluation shows that seven compounds (44575984, 44575990, 469209, 46210307, 21626371, 442023, and 159930) passed the in silico drug‐likeness test and showed high gastrointestinal absorption.…”
Section: Discussionmentioning
confidence: 65%
“…It is known that ADMETox prediction is a significant part in evaluating if a drug can be toxic or absorbed during drug development process [48]. In our study, ADMETox evaluation shows that seven compounds (44575984, 44575990, 469209, 46210307, 21626371, 442023, and 159930) passed the in silico drug‐likeness test and showed high gastrointestinal absorption.…”
Section: Discussionmentioning
confidence: 65%
“…Only ligands which had binding energies equal to or less than − 7.0 kcal.mol −1 from both OEDocking and AutoDock Vina were selected for further studies since this threshold has been shown to distinguish between putative and non-putative binders of proteins [ 41 ]. Although, a more negative binding energy does not imply a better inhibition [ 54 , 55 ], previous studies have shown that ~ 97.7% of known inhibitors have binding energies of − 7.0 kcal.mol −1 or less [ 41 , 56 ] and this threshold filters ~ 95% of non-inhibitors. Other studies have also used the − 7.0 kcal.mol −1 threshold to prioritize compounds [ 57 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…UDP-Galf derivatives are suitable inhibitors of these enzymes, whereby they cause premature galactan chain termination. 79 …”
Section: Pg Synthesis Inhibitormentioning
confidence: 99%